Aerosol–light interactions reduce the carbon budget imbalance. (17th December 2021) - O'Sullivan, Michael; Zhang, Yuan; Bellouin, Nicolas; Harris, Ian; Mercado, Lina M; Sitch, Stephen; Ciais, Philippe; Friedlingstein, Pierre
Abstract: Current estimates of the global land carbon sink contain substantial uncertainties on interannual timescales which contribute to a non-closure in the global carbon budget (GCB) in any given year. This budget imbalance (BIM) partly arises due to the use of imperfect models which are missing or misrepresenting processes. One such omission is the separate treatment of downward direct and diffuse solar radiation on photosynthesis. Here we evaluate and use an improved high-resolution (6-hourly), gridded dataset of surface solar diffuse and direct fluxes, over 1901–2017, constrained by satellite and ground-level observations, to drive two global land models. Results show that tropospheric aerosol–light interactions have the potential for substantial land carbon impacts (up to 0.4 PgCyr-1 enhanced sink) at decadal timescales, however large uncertainties remain, with models disagreeing on the direction of change in carbon uptake. On interannual timescales, results also show an enhancement of the land carbon sink (up to 0.9 PgCyr-1) and subsequent reduction in BIM by 55% in years following volcanic eruptions. We therefore suggest GCB assessments include this dataset in order to improve land carbon sink estimates.